Pengembangan Local Instructional Theory Pada Topik Pembagian dengan Pendekatan Matematika Realistik - Ahmad Fauzan; Yerizon Yerizon; Fridgo Tasman; Rendy Novri Yolanda (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2020)
This research aimed to develop local instruction theory that is valid, practical, and effective to help elementary school students developing their mathematical problem-solving skills. Therefore a sequential activityis design on dailybasis to encourage students to develop their ability to solve mathematical problems, especially on the topic division. To achieve the goal, realistic mathematics approach was implemented to grade three elementary students in the learning process. The designed activities were validated by experts on the aspects of mathematical contents, language, didactical process based on realistic mathematical approach. Data were analyzed with descriptive statistics and parametric statistics. The validation results show that the local instruction theory was valid, and the implementation shows that the local instruction theory is practical and effective in improving students' mathematical problem-solving skills.